Pengaruh Nilai Tukar Rupiah dan Suku Bunga Terhadap Indeks Harga Saham Gabungan (Studi Bursa Efek Indonesia Periode 2019-2023) - Yanuar, Moh David; Khalikussabir, Khalikussabir; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ The main objective of this research is to ascertain the impact of the rupiah exchange rate and self-proclaimed interest rates on the IHSG. Using a quantitative approach, this research uses an explanatory framework. This study targets the IDX for the 2019-2023 period. A purposive sampling method was used to select 60 participants for the research. Information collection was carried out using secondary data where data was taken from existing documents and then developed and further analysis was carried out through Statistical Program Social Science (SPSS) version 26 using multiple linear regression. The findings of this research indicate that the combination of the rupiah exchange rate and self-claimed interest rates has a significant impact on the IHSG.Â Keywords: Rupiah Exchange Rate, Interest Rate, IHSG